Retail foodservice employees’ perceptions of barriers and motivational factors that influence performance of safe food behaviors - Strohbehn, Catherine H.; Shelley, Mack; Arendt, Susan W.; Correia, Ana Paula; Meyer, Janell; Ungku Zainal Abidin, Ungku Fatimah; Jun, Jinhyun (International Association for Food Protection, 2014)
This study identified the barriers and motivational factors that influence nonsupervisory foodservice employees’ decisions to perform safe food handling behaviors. Responses to a bilingual questionnaire were received from 1,103 employees working in four types of retail foodservice. Respondents rated 8 of 16 listed barriers as important obstacles in keeping them from handling food safely, including “the work pace” (mean = 4.28 on a 5-point scale, where 1 = Not Important and 5 = Very Important) and “lack of good habits” (mean = 4.19). Using the same scale, respondents assessed importance of 27 listed items that encourage them to follow safe practices. Of the 27 items, 23 were rated at a mean of 4.0 or higher. The item rated highest was “Keeping customers safe from food-related diseases,” (mean of 4.91), and the item rated lowest (mean of 3.39) was “An unsupportive work group.” Results show employees know what behaviors are considered proper to ensure the safety of food; however, real barriers exist, such as time pressures and habits that are not compatible with safe food practices, suggesting that improved organization and routinization of safe food handling practices in a work culture that values food safety would reduce the risk of foodborne illness.